A method for calculating the external costs of farm animal welfare based on the Welfare Quality® Protocol - Vissers, Luuk S. M.; van Wagenberg, Coen P. A.; Baltussen, Willy H. M. (Frontiers in Animal Science, 2023)
The production of food from animals poses societal concern about the welfare of these animals in Western countries and increasingly also in economically developing countries. Animals and people may experience disutility from animal suffering, which can be seen as an external cost that is not (fully) included in the cost of production. Thus, consumers will consume too much of the good from an aggregate utilitarian perspective. A potential way to solve this issue is by including these external costs in the production costs. The aim of this paper was to provide a method that can be used to estimate the external costs of animal welfare (AW) of animals kept at farm level. The external costs were calculated by means of a cost function. This cost function shows the relationship between the AW score and costs of AW measures at farm level. The AW scores were calculated from principle scores of the Welfare Quality® Protocol. The method was applied to three case studies, namely dairy cattle production in Germany, pig production in the Netherlands, and broiler production in the Netherlands. The results indicate that the external costs of AW of dairy cattle systems ranged from 0.02 to 0.10 euro/kg milk, those of pig production systems from 1.00 to 1.36 euro/kg live weight and those of broiler production systems from 3.67 to 4.52 euro/kg live weight. The empirical application showed that the method was effective in estimating external animal costs. The insights obtained from the application of our method can support decision making in the development and adoption of more AW friendly production systems.